Pemberdayaan Masjid “Pembentukan Program Keluarga Sakinah Berkelanjutan di Masjid Darussalam” - Mochammad Arifin; Erdi Auliya Azzahra (LP3M IAIFA Kediri, 2024)
Empowerment of mosques involves revitalizing their functions, roles, or activities to extend beyond individual acts of worship. This empowerment aims to be conceptualized, implemented, and sustained across religious, educational, and social service domains. Particular attention must be given to family-related aspects, considering the increasing issues in family resilience, which no longer stem solely from economic factors. Concerns such as underage marriages contrary to legal regulations, domestic violence, disputes over shared assets, inheritance, guardianship, and social services like zakat, infaq, sadaqah, and waqf are prevalent. These issues fall within the scope of Islamic Family Law, emphasizing the urgent need for its development as a solution aligned with the goals of mosque empowerment.Masjid Darussalam, located in Doko Village, Doko Sub-district, Blitar Regency, has conducted numerous socio-religious activities. However, these activities have yet to address aspects related to the